Prediction of two bladed horizontal axis wind turbine acoustics - KURULTAY, A. Alper; ALPMAN, Emre (My University, 2016)
Wind power industry has been a growing market and maturing technology for several decades. Increasing wind power generation necessitates closer installation of wind turbines to people and their residences. For that reason, wind turbine noise becomes a serious and controversial phenomenon and it is anticipated to become more stringent issue while wind power generation is increased recently. The aim of this study was to propose a methodology to predict the wind turbine blade noise by using two dimensional blade section flows and noise analysis/simulation and combining the noise sources to evaluate the total blade noise with reasonable accuracy. Within the scope of this work, the purpose was to perform a two dimensional flow and noise simulation for the two bladed NREL Phase VI wind turbine with the aid of a commercially available Computational Fluid Dynamics (CFD) software ANSYS-FLUENT by using User Defined Functions after applying some corrections under certain assumptions. Analysis results were compared with the 12% scaled model of NREL Phase VI wind turbine acoustic noise measurements conducted in In Korea Aerospace Research Institute (KARI) at the low speed wind tunnel. Blade noise of the measurements were compared with the analysis results at different wind speeds of 5.4 m/s, 7.4 m/s, 12.3 m/s, and 13.3 m/s. For the tip region and inboard area of the blade, reasonable agreement was achieved at certain wind speeds. Additionally, the summation of the contribution from the each blade section was used to predict the total noise emission.
Keywords: Wind Turbine Noise, NREL Phase VI, Aero acoustics, Computational Fluid Dynamics.